Navigating digital horizons: A systematic review of social media’s role in destination branding - Deske Wenske Mandagi; Indrajit Indrajit; Toetik Wulyatiningsih (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to acquire a comprehensive understanding of how social media platforms contribute to the process of destination branding by identifying major themes in the literature pertaining to social media's role in destination branding.Method — This study employs a Systematic Literature Review (SLR) methodology to conduct an in-depth analysis of academic journal articles pertaining to the role of Social Media Marketing (SMM) in destination branding. The review encompasses 55 final articles published and indexed in the Scopus database from 2014 to 2024. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method is employed as the framework for this systematic review, ensuring the robustness of the review process.Result — Four prominent themes have been identified regarding the role of SMM in destination branding: 1) Enhancing Destination Brand Value Co-Creation, 2) Influencing Customer-Based Brand Equity, 3) Shaping Destination Brand Identity, and 4) Driving Destination Brand Engagement and Loyalty.Practical implications — Destination marketers should leverage social media strategically to enhance brand visibility, engagement, and loyalty, utilizing these platforms as virtual stages to showcase the destination's culture, heritage, and diversity.